World trauma education: hemorrhage control training for healthcare providers in India. Issue 1 (18th February 2019) - Smith, Lindsay Andrea; Caughey, Sarah; Liu, Susan; Villegas, Cassandra; Kilaru, Mohan; Gupta, Aakanksha; Winchell, Robert J; Narayan, Mayur
Abstract : Background: Hemorrhage remains a major cause of death around the world. Eighty percent of trauma patients in India do not receive medical care within the first hour. The etiology of these poor outcomes is multifactorial. We describe findings from the first Stop the Bleed (StB) course recently offered to a group of medical providers in southern India. Methods: A cross-sectional survey of 101 participants who attended StB trainings in India was performed. Pre-training and post-training questionnaires were collected from each participant. In total, 88 healthcare providers' responses were analyzed. Three bleeding control skills were presented: wound compression, wound packing, and tourniquet application. Results: Among participants, only 23.9% had received prior bleeding control training. Participants who reported feeling 'extremely confident' responding to an emergency medical situation rose from 68.2% prior to StB training to 94.3% post-training. Regarding hemorrhage control abilities, 37.5% felt extremely confident before the training, compared with 95.5% after the training. For wound packing and tourniquet application, 44.3% and 53.4%, respectively, felt extremely confident pre-training, followed by 97.7% for both skills post-training. Importantly, 90.9% of StB trainees felt comfortable teaching newly acquired hemorrhage control skills. A significant majority of participants said that confidence in their wound packing and tourniquet skills would improve with more realistic mannequins. Conclusion: To our knowledge, this is the first StB training in India. Disparities in access to care, long transport times, and insufficient numbers of prehospital personnel contribute to its significant trauma burden. Dissemination of these critical life-saving skills into this region and the resulting civilian interventions will increase the number of trauma patients who survive long enough to reach a trauma center. Additionally, considerations should be given to translating the course into local languages to increase program reach. Level of Evidence: Level IV.